ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI HARGA SAHAM DENGAN NET PROFIT MARGIN SEBAGAI VARIABEL INTERVENING DAN MODERASI PADA PERUSAHAAN KOMPAS100 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 – 2020 - Sulia Sulia; Mie Mie; Riny Riny (DAS Institute, 2022)
The purpose of this study was to determine and analyze the effect of Debt to Equity Ratio (DER), Current Ratio (CR), Total Asset Turnover (TATO), and company size on stock prices with the Net Profile Margin Ratio (NPM) as an intervening variable in the Kompas100 company. listed on the Indonesia Stock Exchange for the 2016-2020 period. In addition, this study also aims to determine and analyze the ability of the Net Profile Margin Ratio (NPM) in moderating the relationship between Debt to Equity Ratio (DER), Current Ratio (CR), Total Asset Turnover (TATO), and company size to stock prices in Kompas100 company listed on the Indonesia Stock Exchange for the 2016-2020 period. The population in this study is the Kompas100 company listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique in this study is to use the Non-Probability Sampling approach with the Purposive Sampling method. The population in this study amounted to 167 companies. From the results of the sample selection obtained as many as 33 companies. The data testing method used is a two-stage approach which consists of the outer model test, feasibility test and inner model test using the SmartPLS version 3.2.9 program. The results of testing the first hypothesis show that the Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) have an effect on the Net Profit Margin Ratio (NPM). While the Current Ratio (CR) and company size have no effect on the Net Profit Margin Ratio (NPM). Total Asset Turnover (TATO) and company size have an effect on stock prices. Meanwhile, Debt to Equity Ratio (DER), Current Ratio (CR), and Net Profit Margin Ratio (NPM) have no effect on stock prices. The results of the second hypothesis testing show that the Debt to Equity Ratio (DER), Current Ratio (CR), Total Asset Turnover (TATO), and company size have no effect on stock prices with the Net Profit Margin Ratio (NPM) as an intervening variable in the Kompas100 company which listed on the Indonesia Stock Exchange for the period 2016-2020. The results of testing the third hypothesis show that the Net Profit Margin Ratio (NPM) is not able to moderate the relationship between Debt to Equity Ratio (DER), Current Ratio (CR), Total Asset Turnover (TATO), and company size to stock prices at Kompas100 companies listed in Indonesia Stock Exchange 2016-2020 period.